Engagement of the contralateral limb can enhance the facilitation of motor output by loud acoustic stimuli - McInnes, Aaron Nicholas; Nguyen, An; Carroll, T.J.; Lipp, Ottmar; Marinovic, Welber (AMER PHYSIOLOGICAL SOC, 2022)
When intense sound is presented during light muscle contraction, inhibition of the corticomotoneuronal pathway is observed. During action preparation, this effect is reversed, with sound resulting in excitation of the corticomotoneuronal pathway. We investigated how the combined maintenance of a muscle contraction during preparation for a ballistic action impacts the magnitude of the facilitation of motor output by a loud acoustic stimulus (LAS), a phenomenon known as the StartReact effect. Participants executed ballistic wrist flexion movements and a LAS was presented simultaneously with the imperative signal in a subset of trials. We examined whether the force level or muscle used to maintain a contraction during preparation for the ballistic response impacted reaction time and/or the force of movements triggered by the LAS. These contractions were sustained either ipsilaterally or contralaterally to the ballistic response. The magnitude of facilitation by the LAS was greatest when low-force flexion contractions were maintained in the limb contralateral to the ballistic response during preparation. There was little change in facilitation when contractions recruited the contralateral extensor muscle or when they were sustained in the same limb that executed the ballistic response. We conclude that a larger network of neurons that may be engaged by a contralateral sustained contraction prior to initiation may be recruited by the LAS, further contributing to the motor output of the response. These findings may be particularly applicable in stroke rehabilitation, where engagement of the contralesional side may increase the benefits of a LAS to the functional recovery of movement.